ANALISIS MINAT BELAJAR MATEMATIKA SISWA KELAS II SD NEGRI 59 LUBUKLINGGAU MENGGUNAKAN MEDIA BELAJAR PUZZLE PADA MATERI BANGUN RUANG - Arini Dwi Swandari; Arif Hidayat; Episiasi Episiasi (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This research aims to determine "ANALYSIS OF INTEREST IN LEARNING MATHEMATICS OF CLASS II STUDENTS OF STATE PRINCIPAL 59 LUBUKLINGGAU USING PUZZLE LEARNING MEDIA ON SPACE BUILDING MATERIALS". This type of research uses qualitative research, namely a research technique that obtains descriptive data based on the percentage of answers from students consisting of 2 indicators of learning interest through questionnaires completed by students. The population in this study was all class II students while the sample used was class II A. The non-test instrument in this research was a questionnaire. The results obtained from 24 class II students were 4 people who still had little interest in the mathematics learning process with spatial material and 20 students had shown their interest in the learning process. In this way, using puzzle learning media to increase interest in learning in mathematics subjects with spatial material can be said to have succeeded in increasing interest in learning.